(3eLed GdCUhd aj CMcGe GdfLhes - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3Efi LeYJ ai gPG GdcJGH ef CUhd UfGYI GdCMcGe hLedi hGdWQb Edi GdJUQa ajgG hGSJYeGdgG heG XffJg cGajkG s
(3BNQgG (B:s
(3hdG JYLd HGdMce EdG HYO GdacQI GdWhjdI hGdfXQ GdcKjQ hGdJCed GdTGai s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B222 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B93 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1604s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B120) s
Keywords: (3Gdadcs